If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9(1 + 7b) = -32 (1 * -9 + 7b * -9) = -32 (-9 + -63b) = -32 Solving -9 + -63b = -32 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -63b = -32 + 9 Combine like terms: -9 + 9 = 0 0 + -63b = -32 + 9 -63b = -32 + 9 Combine like terms: -32 + 9 = -23 -63b = -23 Divide each side by '-63'. b = 0.3650793651 Simplifying b = 0.3650793651
| 9-4x-6-6x=5 | | 12x-9=5x+40 | | 3x-5(x-5)=-6+5x-11 | | -7+4(7b-2)=209 | | 10-20=-b | | 2r-3.1=1.17 | | 6(2)+24=12y | | 8f=7f-10 | | r+16=30 | | -3+7(1-2x)=-94 | | 4y+11+6y+5=180 | | 4y+11+6y+5=90 | | -4h+10=-3h | | -420=910x+2310 | | N+14=3n | | -60=4(2n-7)-10n | | 7(-3x+6)=126 | | 5+-1(t+3)=-1+2(t-3) | | 6(-2)+24=-12y | | 7(-3+6)=126 | | 3a+4x=c | | 64+9f=793 | | x=2y^2-3 | | r+16=20 | | x(1/x+2)=14 | | 9-x=3x+7 | | 117-9r=36 | | 138=6(5r-2) | | 2(3x+5)-2(3x-2)=8 | | 3/2(x)-1/2=x+7/6 | | u/31+587=597 | | 172=-4(8x-3) |